Hidden wonders in a spit: Novel technologies for salivary diagnostics - Areeba Shahid; Shivakumar Ganiga Channaiah; Neeta Misra; Sumalatha Masineni Narayanappa (Wolters Kluwer Medknow Publications, 2020)
Oral cancer is a major contributor to death worldwide. This life-threatening disease still lacks inexpensive screening. Novel strategies for early detection and therapy response are required. Saliva, as "mirror of the body," reflects body's physiological and pathological state. Saliva is the epitome of a noninvasive, readily available, and easy to collect, transport, and store "biofluid." Since the emphasis is switching more toward high impact personalized medicine, pioneering "Point-of-care salivary technologies" are being developed. These facilitate biomarker identification, as an alternative to invasive tissue biopsy. The concept that a patient can take a single drop of their own saliva and test it using portable wireless devices like biosensors, actuators, microelectronics, etc., like Oral Fluid NanoSensor Test (OFNASET) for oral cancer detection is being introduced. An upcoming contemporary tool that integrates both therapeutics and diagnostics is "Liquid biopsy." It is a PCR-based sequencing technique that detects circulating tumor cells (CTCs) and fragments of tumor DNA shed into the bloodstream by cells undergoing apoptosis or necrosis. This review focuses on promising futuristic salivary technologies, which shall bring breakthroughs in terms of precision and efficiency. Oral physicians and oncologists will have ease in detecting and shaping diagnosis of oral cancer in near decade and beyond.